Elevating the role of African agri-businesses in climate action: Tools for tracking climate adaptation and measuring impact. - Nowak, Andreea C.; Giombini, Valentina; Rosenstock, Todd (2024)
African small- and medium-sized agribusiness enterprises (agri-SMEs) report that capacity building in impact pathway development has led to shifts in perspectives, practices, and organizational frameworks. Despite their pivotal role in the food system, the impact of these agri-SMEs on farmers and the environment has not been systematically monitored. An innovative approach developed under the AICCRA Project focuses on enhancing the capability of these enterprises to design business impact pathways aligned with climate and sustainable development goals. This initiative empowers agri-SMEs to identify and monitor context-fit and feasible indicators and data systems for effective tracking of climate-adaptation related impacts.